Lead-acid battery
The lead-acid battery design addresses stratification issues by using barium sulfate particles with controlled size distribution and a separator with optimized crystallinity and pore volume, resulting in improved IS lifetime performance.
Patent Information
- Application Number
- JP2021154669
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-22
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-09-22
AI Technical Summary
Lead-acid batteries experience stratification of sulfate ions, leading to deterioration of the negative electrode plate and reduced IS lifetime performance, especially in undercharged conditions like idling stop applications.
A lead-acid battery design featuring a negative electrode plate with barium sulfate particles of controlled particle size distribution, a separator with a crystalline region and amorphous region, and a specific pore volume configuration to enhance electrolyte diffusivity and oxidation resistance.
The solution significantly improves the IS lifetime performance of lead-acid batteries by reducing stratification, enhancing charge acceptance, and minimizing oxidation deterioration of the separator.
Smart Images

Figure 0007661855000002 
Figure 0007661855000003 
Figure 0007661855000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a lead-acid battery. [Background technology]
[0002] A lead-acid battery includes a positive electrode plate, a negative electrode plate, a separator interposed between the positive electrode plate and the negative electrode plate, and an electrolyte. One of the typical applications of lead-acid batteries is in automobiles. In automobile applications, the load of electrical equipment has increased in line with recent improvements in performance, and further improvements in performance are required for lead-acid batteries. For this reason, there is a demand for battery designs that take into account the overall action of the components of a lead-acid battery, including improvements in components such as separators and plates.
[0003] For example, Patent Document 1 proposes a separator for a lead acid battery comprising a polyolefin microporous membrane, the polyolefin microporous membrane comprising polyethylene, preferably ultra-high molecular weight polyethylene, a particulate filler, and a treatment plasticizer, the particulate filler being present in an amount of 40% or more by weight, the polyethylene comprising a shish-kebab-formed polymer comprising a plurality of extended chain crystals (shish formation) and a plurality of folded chain crystals (kebab formation), the average repetition or period of the kebab formation being from 1 nm to 150 nm, preferably less than 120 nm.
[0004] Patent Document 2 proposes a lead-acid battery including a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, in which the negative electrode has a negative electrode material including a chemically treated mixture containing a raw material for a negative electrode active material and particles containing barium, the particles having an average primary particle size of 0.10 μm or less before chemical treatment, and the electrolyte contains aluminum ions.
[0005] Patent Document 3 proposes a negative electrode plate for a lead-acid battery that contains barium sulfate, the barium sulfate including at least a first particle group and a second particle group, the first particle group having a primary particle diameter of 10 μm or less with an average value of 0.3 μm or more and 0.9 μm or less, the second particle group having a primary particle diameter of 10 μm or less with an average value of 2 μm or more and 5 μm or less, and the first particle group accounting for 28% or more and 72% or less of the total amount of barium sulfate on a volume frequency basis. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Special Publication No. 2019-514173 [Patent Document 2] International Publication No. 2018 / 100635 [Patent Document 3] JP 2015-109171 A Summary of the Invention [Problem to be solved by the invention]
[0007] In lead-acid batteries, stratification is likely to occur during charging, when sulfate ions, which have a large specific gravity, descend and cause a difference in the specific gravity of the electrolyte (i.e., a difference in the concentration of sulfuric acid) between the upper and lower parts of the battery container. Stratification becomes more pronounced when lead-acid batteries are used in a partially charged state called a partial state of charge (PSOC). For example, in idle stop (IS) (also called idle reduction) applications such as vehicles with idling stop systems, or in charge control applications, lead-acid batteries are used in PSOC, so stratification is likely to become more pronounced. When stratification becomes more pronounced, the negative plate deteriorates, and the life performance (also called IS life performance) of the lead-acid battery when used in PSOC decreases.
[0008] Increasing the pore volume of the separator improves the diffusion of the electrolyte, which is expected to be advantageous in terms of suppressing stratification. However, the contact area with the electrolyte increases, which makes the separator more susceptible to oxidation degradation. Damage to the separator causes a short circuit, which ends its life, so the effect of improving IS life performance is limited.
[0009] In addition, lead sulfate is formed in the negative electrode plate of a lead-acid battery during discharge. When the lead sulfate particles become coarse, it becomes difficult to reduce lead sulfate to lead during charging, and the charge acceptance decreases. This causes further stratification and reduces capacity. This also reduces the IS life performance. [Means for solving the problem]
[0010] One aspect of the present disclosure is a lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate, the negative plate comprises a negative electrode material including barium sulfate particles; In the volume-based particle size distribution of the barium sulfate particles, when the particle sizes at which the cumulative frequency is 10%, 50% and 90% are D10, D50 and D90, respectively, the span value represented by (D90-D10) / D50 is 2.78 or less; The separator includes a crystalline region and an amorphous region, In the X-ray diffraction spectrum of the separator, 100×I c / (I c +I a ) has a crystallinity of 20% or more, I c is the integrated intensity of the diffraction peak having the maximum peak height among the diffraction peaks corresponding to the crystalline region, I a is the integrated intensity of the halo corresponding to the amorphous region, In the separator, the total volume Vt of the pores having a pore diameter of 0.005 μm or more and 10 μm or less is 0.8 cm 3 / g or more. Effect of the Invention
[0011] We can provide a lead-acid battery that provides excellent IS life performance. [Brief description of the drawings]
[0012] [Figure 1] 1 is a partially cutaway perspective view showing the appearance and internal structure of a lead-acid battery according to one embodiment of the present invention; [Diagram 2] 1 is an X-ray diffraction spectrum of a separator for a lead-acid battery E1 of an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Various studies have been conducted with the aim of improving the IS life performance of lead-acid batteries. To some extent, using a separator with a large pore volume is effective in suppressing stratification. In IS applications, constant voltage charging is performed, and the current flow increases, generating gas, and when the gas diffuses through many pores in the separator, the effect of mixing the electrolyte is obtained. However, on the other hand, the contact area between the separator and the gas increases, and the contact opportunity increases, making it easier for the separator to undergo oxidative deterioration. In addition, as the softening of the positive electrode material progresses, it becomes easier for the separator to break when the fallen positive electrode material comes into contact with the separator. From these perspectives, the chances of short circuiting of the separator increase, and the IS life performance decreases. Therefore, if the oxidative deterioration can be suppressed while maintaining the large pore volume of the separator, it is effective in improving the IS life performance.
[0014] In the negative plate, if the coarsening of lead sulfate that is generated during discharge can be suppressed, it is believed that the charge acceptance will improve and the reduction of lead sulfate to lead during charging can proceed smoothly. If the charge / discharge reaction in the negative plate proceeds more uniformly across the entire plate, the charge / discharge reaction in the positive plate will tend to proceed more uniformly. This will prevent stratification from progressing and suppress the decrease in capacity, which is believed to be advantageous in improving IS life performance.
[0015] The negative electrode material may contain barium sulfate particles as an additive. In this case, during discharge, lead sulfate is formed in the negative plate with the barium sulfate particles as nuclei. This can reduce the generation of coarse lead sulfate particles during discharge to some extent. However, if the particle size of the barium sulfate nuclei varies widely, the particle size of the lead sulfate produced tends to vary widely. If the particle size of the lead sulfate varies widely, the reactivity during charging varies.
[0016] In view of the above, a lead-acid battery according to one aspect of the present invention includes at least one cell including an electrode plate group and an electrolyte. The electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate. The negative electrode plate includes a negative electrode material including barium sulfate particles. In the volume-based particle size distribution of the barium sulfate particles, particle sizes at which the cumulative frequency is 10%, 50%, and 90% are defined as D10, D50, and D90, respectively. In this case, the span value expressed by (D90-D10) / D50 is 2.78 or less. In addition, the separator includes a crystalline region and an amorphous region. In an X-ray diffraction (XRD) spectrum of the separator, 100×I c / (I c +I a ) is 20% or more. c is the integrated intensity of the diffraction peak having the maximum peak height (hereinafter sometimes referred to as the first diffraction peak) among the diffraction peaks corresponding to the crystalline region, and I a is the integrated intensity of the halo corresponding to the amorphous region. The total volume of the pores with diameters between 0.005 μm and 10 μm, Vt, is 0.8 cm 3 / g or more. Hereinafter, pores having a pore diameter of 0.005 μm or more and 10 μm or less may be referred to as first pores. The total volume Vt of the first pores may be simply referred to as the first pore volume Vt.
[0017] The span value of barium sulfate particles represents the degree of variation in particle size. When the variation in particle size of barium sulfate particles becomes large, the reduction of lead sulfate to lead becomes difficult in lead sulfate with a large particle size, while the reduction occurs smoothly in lead sulfate with a small particle size. Even if the charge is performed for the same time, the amount of lead sulfate reduced to lead decreases, resulting in a decrease in charge capacity. As a result, the discharge reaction also varies, and the discharge capacity also decreases. In addition, as the variation in particle size of barium sulfate particles increases, the IS life performance tends to decrease. In particular, when the span value exceeds 2.78, the decrease in IS life performance is likely to be significant. This tendency for the IS life performance to decrease with an increase in the span value is also seen when the crystallinity of the separator is 20% or more.
[0018] However, when the span value of the barium sulfate particles in the negative electrode material is 2.78 or less, the crystallinity is 20% or more, and the total volume of the first pores Vt (first pore volume Vt) is 0.8 cm 3 When combined with a separator with a rating of 0.1% or more, the IS life performance is significantly improved.
[0019] More specifically, first, when the span value of the barium sulfate particles is 2.78 or less, the variation in particle size of lead sulfate formed during discharge is relatively small. Therefore, during charging, the variation in the progress of the reduction reaction from lead sulfate to lead is reduced, the charge acceptance is improved, and the charging reaction occurs more uniformly. When charging for the same time, more lead sulfate can be reduced to lead than when the span value exceeds 2.78. In addition, the variation in the charging reaction in the negative plate is reduced, so that the charging reaction in the positive plate is also reduced, making it easier for the charging reaction to proceed overall.
[0020] At that time, the total volume Vt of the first pores in the separator (first pore volume Vt) is 0.8 cm 3 / g or more, high diffusivity of the electrolyte can be obtained and the resistance of the separator can be suppressed low. Therefore, the effect of suppressing stratification is enhanced. Therefore, in addition to the charging characteristics improved by reducing the variation in particle diameter of the barium sulfate particles, the charge / discharge reaction in the negative electrode proceeds smoothly. However, when the first pore volume Vt is in the above range, the contact area with the electrolyte increases, so that the oxidative deterioration of the separator tends to progress easily. In a lead-acid battery, when the separator is oxidatively deteriorated, the flexibility decreases and cracks occur, causing a short circuit and resulting in the end of life. Even if stratification can be reduced, the effect of improving IS life performance is limited. In contrast, in the above aspect of the present invention, since the crystallinity is 20% or more, the oxidation resistance of the separator itself can be increased. Therefore, by reducing the oxidative deterioration of the separator, the deterioration of IS life performance due to a short circuit is suppressed, and the effect of improving IS life performance due to the small variation in particle diameter of the barium sulfate particles and the effect of improving IS life performance due to the suppression of stratification by the separator are fully exhibited. As a result, excellent IS life performance can be ensured.
[0021] In addition, the first pore volume Vt is 0.8 cm 3 When the crystallinity is less than 0.8 cm3 / g, the IS life performance remains almost unchanged even if the crystallinity is changed. In this case, the small surface area of the separator reduces contact with the electrolyte, suppressing oxidation degradation, and stratification becomes prominent, resulting in the end of life. Therefore, it is considered that increasing the crystallinity of the separator does not affect the IS life performance. Thus, when the first pore volume Vt is 0.8 cm3, the IS life performance remains almost unchanged even if the crystallinity is increased. 3 / g and 0.8cm 3 / g or more, the behavior of IS life performance when the crystallinity of the separator is changed is completely different.
[0022] Unlike separators for lithium ion secondary batteries, etc., separators for lead acid batteries have a certain degree of thickness. In addition, the thicker the separator, the more difficult it tends to be to increase the crystallinity. In addition, as the crystallinity increases, the separator tends to become hard and brittle. From this viewpoint, the crystallinity of conventional separators for lead acid batteries has not been controlled. The crystallinity of conventional separators for lead acid batteries tends to be relatively low, for example, about 18% or less. In contrast to such conventional common sense, according to a lead acid battery according to one aspect of the present invention, the first pore volume Vt is 0.8 cm 3 It was revealed that when the crystallinity is 20% or more and the barium sulfate particles have a span value of 2.78 or less, the IS life performance can be significantly improved by combining a separator with a crystallinity of 20% or more with a negative electrode plate with a span value of 2.78 or less.
[0023] The total volume Vt of the first pores in the separator (first pore volume Vt) is the sum of the volumes of the first pores (pores having a pore diameter of 0.005 μm or more and 10 μm or less) in the separator determined by mercury intrusion porosimetry.
[0024] The volumetric particle size distribution of barium sulfate particles is a volumetric particle size distribution measured by a laser diffraction or scattering type particle size distribution measuring device. The particle sizes at which the cumulative frequency (integrated value) in this volumetric particle size distribution is 10%, 50%, and 90% are D10, D50, and D90, respectively. The particle size D50 corresponding to 50% of the integrated value in the volumetric particle size distribution is also called the median size. In this specification, the particle size of barium sulfate particles refers to the particle size of the primary particles.
[0025] From the viewpoint of easily obtaining higher IS life performance, the span value is preferably equal to or less than 2.75, and more preferably equal to or less than 2.45.
[0026] The first pore volume Vt is 0.90 cm 3 When the crystallinity of the separator is less than 20%, the first pore volume Vt is preferably 0.8 cm 3 / g, the IS life performance is high, but the span value is small and Vt is 0.8cm 3 / g or more, the IS life performance decreases. This is because the crystallinity is low and the oxidative degradation of the separator becomes significant as the Vt increases. On the other hand, when the crystallinity is 20% or more, the IS life performance increases as the span value of the barium sulfate particles decreases. In addition, high IS life performance is easily obtained because the separator has higher oxidation resistance.
[0027] The crystallinity may be 40% or less, which makes it easier to ensure the flexibility of the separator and facilitates manufacturing.
[0028] The separator preferably contains a polyolefin, more preferably a polyolefin containing at least an ethylene unit. Such a separator is prone to oxidative deterioration, but the crystallinity can be increased relatively easily. When the separator contains a polyolefin containing at least an ethylene unit, the first diffraction peak corresponds to the (110) plane due to the crystalline region.
[0029] The thickness of the separator is preferably 100 μm or more and 300 μm or less. When the thickness is in this range, the effect of suppressing oxidative degradation of the separator is further enhanced, and the IS life performance can be further improved.
[0030] The separator preferably contains oil, which further enhances the effect of suppressing oxidation degradation of the separator, thereby ensuring higher IS life performance.
[0031] The lead-acid battery may be a valve regulated battery, but is preferably a flooded battery (vented battery), which is sometimes called a Valve Regulated Lead-Acid Battery (VRLA).
[0032] In this specification, the up-down direction of a lead-acid battery or components of the lead-acid battery (such as plates, battery case, separator, etc.) refers to the up-down direction in the vertical direction of the lead-acid battery when the lead-acid battery is in use. Each of the positive and negative plates has a lug for connecting to an external terminal, and in a flooded battery, the lug is provided on the top of the plate so as to protrude upward.
[0033] Hereinafter, a lead-acid battery according to an embodiment of the present invention will be described in more detail with reference to the drawings. However, the present invention is not limited to the following embodiment.
[0034] (Separator) The separator contains crystalline regions in which the molecules of the separator's constituent material are arranged in a relatively regular manner (i.e., highly ordered), and amorphous regions in which the molecules are less ordered. Therefore, in the XRD spectrum of the separator, diffraction peaks due to the crystalline regions are observed, and scattered light due to the amorphous regions is observed as a halo. In the XRD spectrum of the separator, 100×I c / (I c +I a By having a crystallinity of 20% or more, excellent IS life performance can be obtained. c is the integrated intensity of the diffraction peak with the largest peak height (the first diffraction peak) among the diffraction peaks corresponding to the crystalline region, and I a is the integrated intensity of the halo corresponding to the amorphous region.
[0035] For example, in the XRD spectrum of a separator containing a polyolefin containing ethylene units, a diffraction peak corresponding to the (110) plane of the crystalline region is observed in the range of 2θ from 20° to 22.5°, and a diffraction peak corresponding to the (200) plane of the crystalline region is observed in the range of 2θ from 23° to 24.5°. A halo of the amorphous region is observed in the range of 2θ from 17° to 27°. Of the diffraction peaks due to the crystalline region, the diffraction peak corresponding to the (110) plane has the maximum peak height and corresponds to the first diffraction peak.
[0036] The crystallinity is 20% or more, and from the viewpoint of ensuring higher IS life performance, it may be 23% or more or 25% or more. The crystallinity of the separator may be 40% or less, 35% or less, or 30% or less. When the crystallinity is in such a range, it is easy to ensure the flexibility of the separator and also easy to manufacture.
[0037] The crystallinity of the separator may be 20% or more (or 23% or more) and 40% or less, 20% or more (or 23% or more) and 35% or less, 20% or more (or 23% or more) and 30% or less, 25% or more and 40% or less (or 35% or less), or 25% or more and 30% or less.
[0038] The integrated intensities of the diffraction peaks and halos are determined by fitting the diffraction peaks due to the crystalline regions and the halos due to the amorphous regions in the XRD spectrum of the separator. The integrated intensity I c and the integrated intensity of the halo I a The crystallinity is calculated from the above formula using
[0039] The first pore volume Vt in the separator is 0.8 cm 3 / g or more. By setting the first pore volume Vt in this range, high diffusibility of the electrolyte can be obtained and the resistance of the separator can be kept low. Therefore, excellent IS life performance can be obtained. From the viewpoint of ensuring higher IS life performance, the first pore volume Vt is 0.90 cm 3 The first pore volume Vt is, for example, 2.2 cm 3 From the viewpoint that the effect of improving IS life performance by increasing the crystallinity is more easily exhibited, the first pore volume Vt is 2.0 cm 3 / g or less is preferable, and 1.6 cm 3 / g or less or 1.2cm 3 / g or less is more preferable.
[0040] The first pore volume Vt is 0.8 cm 3 / g or more (or 0.90cm 3 / g or more) 2.2cm 3 / g or less, 0.8cm 3 / g or more (or 0.90cm 3 / g or more)2.0cm 3 / g or less, 0.8cm 3 / g or more (or 0.90cm 3 / g or more) 1.6cm 3 / g or less, or 0.8cm 3 / g or more (or 0.90cm 3 / g or more) 1.2cm 3 / g or less.
[0041] The separator includes a polymer material (hereinafter also referred to as a base polymer). Since the separator includes a crystalline region, the base polymer usually includes a crystalline polymer. The separator includes, for example, a polyolefin. A polyolefin is a polymer that includes at least an olefin unit (i.e., a polymer that includes at least a monomer unit derived from an olefin).
[0042] As the base polymer, polyolefin may be used in combination with other base polymers. The ratio of polyolefin to the entire base polymer contained in the separator is, for example, 50% by mass or more, 80% by mass or more, or 90% by mass or more. The ratio of polyolefin is, for example, 100% by mass or less. The base polymer may be composed of only polyolefin. When the ratio of polyolefin is so high, the oxidation resistance of the separator tends to be low, but even in such a case, the crystallinity is set to the above range, so that high IS life performance can be ensured.
[0043] Polyolefins include, for example, homopolymers of olefins, copolymers containing different olefin units, and copolymers containing olefin units and copolymerizable monomer units. The copolymers containing olefin units and copolymerizable monomer units may contain one or more types of olefin units. The copolymers containing olefin units and copolymerizable monomer units may contain one or more types of copolymerizable monomer units. The copolymerizable monomer units are monomer units derived from polymerizable monomers other than olefins and copolymerizable with olefins.
[0044] The polyolefin may, for example, be at least C 2-3 Polymers containing olefins as monomer units are also included. 2-3 The olefin may be at least one selected from the group consisting of ethylene and propylene. The polyolefin may be, for example, polyethylene, polypropylene, C 2-3 Copolymers containing olefin as a monomer unit (e.g., ethylene-propylene copolymer) are more preferred. Among polyolefins, polyolefins containing at least ethylene units (polyethylene, ethylene-propylene copolymer, etc.) are preferably used. Polyolefins containing ethylene units (polyethylene, ethylene-propylene copolymer, etc.) may be used in combination with other polyolefins.
[0045] The separator preferably contains oil. When the separator contains oil, the effect of suppressing oxidative deterioration of the separator can be further enhanced, so that a higher IS life performance can be ensured. The oil refers to a hydrophobic substance that is liquid at room temperature (a temperature of 20°C or more and 35°C or less) and separates from water. The oil includes naturally derived oil, mineral oil, and synthetic oil. As the oil, mineral oil, synthetic oil, etc. are preferable. As the oil, for example, paraffin oil and silicone oil can be mentioned. The separator may contain one type of oil or a combination of two or more types of oil.
[0046] The oil content in the separator may be 11% by mass or more, or 12% by mass or more. The oil content may be 18% by mass or less. When the oil content is in such a range, the effect of suppressing oxidation deterioration of the separator is further enhanced. In addition, the resistance of the separator can be kept relatively low.
[0047] The separator may be in a sheet shape. Also, a sheet folded in an accordion shape may be used as the separator. The separator may be formed in a bag shape. Either the positive electrode plate or the negative electrode plate may be wrapped in the bag-shaped separator.
[0048] The separator may or may not have ribs. A separator having ribs includes, for example, a base portion and ribs standing on the surface of the base portion. The ribs may be provided on only one surface of the separator or each of the base portions, or on both surfaces. The base portion of the separator refers to the portion of the separator that does not include protrusions such as ribs, and is a sheet-like portion that defines the outer shape of the separator.
[0049] The thickness of the separator is, for example, 90 μm or more. From the viewpoint of obtaining higher IS life performance, it is preferable that the thickness is 100 μm or more or 150 μm or more. The thickness of the separator is, for example, 300 μm or less. From the viewpoint of suppressing the resistance of the separator low, the thickness of the separator may be 250 μm or less or 200 μm or less. The thickness of the separator means the average thickness of the part of the separator facing the electrode material. In the case where the separator has a base part and a rib erected from at least one surface of the base part, the thickness of the separator is the average thickness of the base part. In the case where an attachment member (such as a mat or pasting paper) is attached to the separator, the thickness of the attachment member is not included in the thickness of the separator.
[0050] The thickness of the separator may be 90 μm or more and 300 μm or less (or 250 μm or less), 90 μm or more and 200 μm or less, 100 μm or more (or 150 μm or more) and 300 μm or less, 100 μm or more (or 150 μm or more) and 250 μm or less, or 100 μm or more (or 150 μm or more) and 200 μm or less.
[0051] When the separator has ribs, the height of the ribs may be 0.05 mm or more. Also, the height of the ribs may be 1.2 mm or less. The height of the ribs is the height of the parts that protrude from the surface of the base part (protrusion height).
[0052] The height of the ribs provided in the region of the separator facing the positive electrode plate may be 0.4 mm or more.The height of the ribs provided in the region of the separator facing the positive electrode plate may be 1.2 mm or less.
[0053] The separator can be obtained, for example, by extruding a resin composition containing a base polymer, a pore-forming agent, and a penetrating agent (surfactant) into a sheet, stretching the resin composition, and then removing at least a portion of the pore-forming agent. By removing at least a portion of the pore-forming agent, micropores are formed in the matrix of the base polymer. The separator (or the resin composition used to manufacture the separator) may contain inorganic particles. After removing the pore-forming agent, the sheet-shaped separator is dried as necessary. For example, the crystallinity is adjusted by adjusting at least one selected from the group consisting of the cooling rate of the sheet during extrusion molding, the stretching ratio during stretching, and the temperature during drying. For example, the crystallinity tends to increase when the sheet is rapidly cooled during extrusion molding, the stretching ratio is increased, or the temperature during drying is decreased. The stretching may be performed by biaxial stretching, but is usually performed by uniaxial stretching. The sheet-shaped separator may be folded into a bellows shape or processed into a bag shape as necessary.
[0054] In a separator having ribs, the ribs may be formed on the sheet when the resin composition is extruded, or the ribs may be formed by pressing the sheet with a roller having grooves corresponding to each rib after the resin composition is molded into a sheet or after the pore-forming agent is removed.
[0055] The pore structure and first pore volume Vt in the separator can be adjusted by adjusting the affinity between the base polymer and the pore-forming agent and / or penetrant, adjusting the dispersibility of the pore-forming agent, selecting the type and / or particle size of inorganic particles, selecting the type of penetrant, adjusting the amount of inorganic particles, the amount of pore-forming agent, and / or the amount of penetrant, and / or adjusting the amount of functional groups and / or atoms present on the surface of the inorganic particles.
[0056] Examples of the pore-forming agent include liquid pore-forming agents and solid pore-forming agents. The pore-forming agent preferably contains at least oil. By using oil, a separator containing oil is obtained, and the effect of suppressing oxidative deterioration is further enhanced. The pore-forming agent may be used alone or in combination of two or more. Oil may be used in combination with another pore-forming agent. A liquid pore-forming agent may be used in combination with a solid pore-forming agent. At room temperature (a temperature of 20°C or higher and 35°C or lower), a liquid pore-forming agent is classified as a liquid pore-forming agent, and a solid pore-forming agent is classified as a solid pore-forming agent.
[0057] The liquid pore-forming agent is preferably the above-mentioned oil, and the solid pore-forming agent is, for example, a polymer powder.
[0058] The amount of the pore-forming agent in the separator may vary depending on the type. The amount of the pore-forming agent in the separator is, for example, 30 parts by mass or more per 100 parts by mass of the base polymer. The amount of the pore-forming agent is, for example, 60 parts by mass or less per 100 parts by mass of the base polymer.
[0059] For example, a separator containing oil is formed by extracting and removing a part of the oil from a sheet formed using oil as a pore-forming agent using a solvent. The solvent is selected, for example, according to the type of oil. For example, the oil content in the separator is adjusted by adjusting the type and composition of the solvent, extraction conditions (extraction time, extraction temperature, solvent supply rate, etc.), and the like.
[0060] The surfactant as the penetrating agent may be, for example, either an ionic surfactant or a nonionic surfactant. The surfactant may be used alone or in combination of two or more kinds.
[0061] The content of the penetrant in the separator is, for example, 0.01% by mass or more, and may be 0.1% by mass or more. The content of the penetrant in the separator may be 10% by mass or less.
[0062] The inorganic particles are preferably, for example, ceramic particles. Examples of ceramics constituting the ceramic particles include at least one selected from the group consisting of silica, alumina, and titania.
[0063] The content of the inorganic particles in the separator may be, for example, 40% by mass or more.The content of the inorganic particles may be, for example, 80% by mass or less, or 70% by mass or less.
[0064] (Separator analysis or size measurement) (Preparation of separator) For the analysis or size measurement of the separator, an unused separator or a separator taken from a lead-acid battery in a fully charged state at the beginning of use is used. The separator taken from the lead-acid battery is washed and dried prior to the analysis or measurement.
[0065] The separator removed from the lead-acid battery is washed and dried according to the following procedure. The separator is immersed in pure water for one hour to remove the sulfuric acid from the separator. The separator is then removed from the liquid and left to stand for at least 16 hours in an environment of 25°C ± 5°C to dry.
[0066] In this specification, the fully charged state of a flooded lead-acid battery is defined by the definition of JIS D 5301:2019. More specifically, the fully charged state is a state in which a lead-acid battery is charged in a water tank at 25°C ± 2°C with a current (A) that is 1 / 10 of the value listed as the rated capacity, until the terminal voltage (V) during charging measured every 15 minutes or the electrolyte density converted to a temperature of 20°C shows a constant value with three significant digits three consecutive times. In addition, in the case of a valve-regulated lead-acid battery, the fully charged state is a state in which constant current and constant voltage charging is performed at 2.23 V / cell in an air tank at 25°C ± 2°C with a current (A) that is 0.2 times the value (unit: Ah) listed as the rated capacity, and charging is terminated when the charging current during constant voltage charging becomes 0.005 times the value (unit: Ah) listed as the rated capacity. The value listed as the rated capacity is a value in Ah. The unit of current set based on the value stated as the rated capacity is A.
[0067] A fully charged lead-acid battery is a lead-acid battery that has already been chemically formed and is fully charged. The lead-acid battery may be fully charged immediately after chemical formation, or after a certain period of time has passed since chemical formation (for example, a lead-acid battery that is in use (preferably in the early stages of use) after chemical formation may be fully charged).
[0068] In this specification, a battery in its early stages of use refers to a battery that has not been in use for a long time and has hardly deteriorated at all.
[0069] (XRD spectrum) The XRD spectrum of a separator is measured by irradiating the separator with X-rays perpendicular to its surface. The measurement sample is prepared by processing the part of the separator facing the electrode material into a strip. For separators with ribs, the base part is processed into a strip so as not to include the ribs. The measurement and fitting of the XRD spectrum are performed under the following conditions. (Measurement conditions) Measurement device: RINT-TTR2, manufactured by Rigaku Corporation Fitting: FT (step scan) method Measurement angle range: 15-35° Step width: 0.02° Measurement speed: 5° / min XRD data processing: XRD pattern analysis software (PDXL2, Rigaku Corporation) was used.
[0070] (First pore volume Vt) The portion of the separator facing the electrode material is processed into a 20 mm x 5 mm strip to prepare a sample (hereinafter referred to as Sample A). For separators having ribs, Sample A is prepared by processing the base portion into a strip so as not to include the ribs. For Sample A, a mercury porosimeter is used to determine the pore distribution under the following conditions, and Vt is calculated by adding up the volumes of the first pores. Mercury porosimeter: Autopore IV9510, manufactured by Shimadzu Corporation Measurement pressure range: 4 psia (≒ 27.6 kPa) to 60,000 psia (≒ 414 MPa) Pore size distribution: 0.01μm to 50μm
[0071] (Separator thickness and rib height) The thickness of the separator is determined by measuring the thickness at five arbitrarily selected points in a cross-sectional photograph of the separator and averaging the measurements.
[0072] The height of the rib is determined by averaging the heights of the base portion of the rib from one surface, measured at 10 arbitrarily selected points on the rib in a cross-sectional photograph of the separator.
[0073] (Oil content in the separator) The portion of the separator facing the electrode material is processed into a rectangular shape to prepare a sample (hereinafter referred to as Sample B). For separators having ribs, Sample B is prepared by processing the base portion into a rectangular shape so as not to include the ribs.
[0074] Approximately 0.5 g of sample B is taken and accurately weighed to determine the initial mass of the sample (m0). The weighed sample B is placed in a glass beaker of appropriate size, and 50 mL of n-hexane is added. Next, ultrasonic waves are applied to the sample together with the beaker for approximately 30 minutes to dissolve the oil contained in sample B into n-hexane. Next, the sample is removed from n-hexane, dried in air at room temperature (temperature between 20°C and 35°C), and then weighed to determine the mass (m1) of the sample after removing the oil. Then, the oil content is calculated using the following formula. The oil content of 10 samples B is calculated and the average value is calculated. The obtained average value is regarded as the oil content in the separator. Oil content (mass%) = (m0-m1) / m0 x 100
[0075] (Content of inorganic particles in separator) A portion of sample B prepared in the same manner as above is taken, accurately weighed, and then placed in a platinum crucible and heated with a Bunsen burner until no more white smoke is emitted. The sample obtained is then heated in an electric furnace (in oxygen flow, 550°C ± 10°C) for approximately 1 hour to be incinerated, and the incinerated material is weighed. The ratio (percentage) of the mass of the incinerated material to the mass of sample B is calculated, and this is taken as the inorganic particle content (mass%) described above. The inorganic particle content is determined for 10 samples B, and the average value is calculated. The obtained average value is taken as the inorganic particle content in the separator.
[0076] (Percentage of penetrant in separator) A portion of sample B prepared in the same manner as above is taken, accurately weighed, and then dried for 12 hours or more at room temperature (temperature between 20°C and 35°C) in a reduced pressure environment lower than atmospheric pressure. The dried material is placed in a platinum cell and set in a thermogravimetric measuring device, and the temperature is raised from room temperature to 800°C ± 1°C at a heating rate of 10K / min. The weight loss amount when the temperature is raised from room temperature to 250°C ± 1°C is taken as the mass of the penetrant, and the ratio (percentage) of the mass of the penetrant to the mass of sample B is calculated, and this is taken as the content (mass%) of the penetrant. A Q5000IR manufactured by TA Instruments is used as the thermogravimetric measuring device. The content of the penetrant is determined for 10 pieces of sample B, and the average value is calculated. The obtained average value is taken as the content of the penetrant in the separator.
[0077] (Negative plate) The negative electrode plate of a lead-acid battery is composed of a negative current collector and a negative electrode material. The negative electrode material is the portion of the negative electrode plate excluding the negative current collector. Note that an attachment member as described above may be attached to the negative electrode plate. In this case, the attachment member is included in the negative electrode plate. In the case where the negative electrode plate includes an attachment member, the negative electrode material is the portion of the negative electrode plate excluding the negative current collector and the attachment member.
[0078] The negative electrode current collector can be formed in the same manner as the positive electrode current collector. At least one of the positive electrode current collector and the negative electrode current collector may be a current collector formed by an expanding process.
[0079] The lead alloy used in the negative electrode current collector may be any of Pb-Sb alloy, Pb-Ca alloy, and Pb-Ca-Sn alloy. These lead or lead alloys may further contain at least one selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. as an additive element. The negative electrode current collector may have lead alloy layers with different compositions, and the alloy layer may be one layer or multiple layers.
[0080] The negative electrode material contained in the negative plate contains barium sulfate particles. The negative electrode material usually contains a negative electrode active material (lead or lead sulfate) that exhibits capacity through an oxidation-reduction reaction, and may contain an organic shrinkage inhibitor, a carbonaceous material, etc. The negative electrode material may contain other additives (such as a reinforcing material) as necessary.
[0081] The span value of the barium sulfate particles, expressed by (D90-D10) / D50, is 2.78 or less. If the span value exceeds 2.78, the effect of improving IS life performance is hardly obtained. From the viewpoint of obtaining higher IS life performance, the span value is preferably 2.75 or less or 2.73 or less, and more preferably 2.45 or less or 2.42 or less. 3 When combined with a separator having a crystallinity of 20% or less and a molecular weight of 1.0 / g or more, the smaller the span value of the barium sulfate particles in the negative electrode material, the higher the IS life performance tends to be. However, it is technically difficult to reduce the span value. The lower limit of the span value is not particularly limited, and may be, for example, 2 or more.
[0082] In the negative electrode material, the D50 (average particle size) of the barium sulfate particles is 1 μm or less, may be 0.7 μm or less, or may be 0.4 μm or less. When the D50 is in such a range, lead sulfate is likely to grow around the barium sulfate particles as nuclei, and the span value is easily adjusted to a suitable range. In addition, the aggregation of the barium sulfate particles is easily suppressed, and the handling can be improved. The average particle size of the barium sulfate particles is, for example, 0.01 μm or more.
[0083] In the negative electrode material, the barium sulfate particles may have a D90 of 2.5 μm or less, 2.0 μm or less, or 1.7 μm or less. When the D90 is in such a range, the span value is easily reduced. The barium sulfate particles may have a D90 of 1.0 μm or more.
[0084] In the negative electrode material, the barium sulfate particles may have a D10 of 0.25 μm or less, 0.24 μm or less, or 0.22 μm or less. When the D10 is in such a range, it is easy to adjust the span value to an appropriate range. The barium sulfate particles may have a D10 of 0.01 μm or more.
[0085] The content of barium sulfate particles in the negative electrode material is, for example, 0.1% by mass or more, preferably 0.5% by mass or more or 1% by mass or more. When the content of barium sulfate particles is in such a range, the barium sulfate that becomes the core of lead sulfate during discharge is present in an appropriate amount, so that a more uniform discharge reaction is likely to proceed. In addition, the content of barium sulfate particles in the negative electrode material is, for example, 7.5% by mass or less, preferably 5.3% by mass or less. In this case, a high initial capacity can be ensured.
[0086] The content of barium sulfate particles in the negative electrode material may be 0.1% by mass or more and 7.5% by mass or less (or 5.3% by mass or less), 0.5% by mass or more and 7.5% by mass or less (or 5.3% by mass or less), or 1% by mass or more and 7.5% by mass or less (or 5.3% by mass or less).
[0087] Examples of the organic shrinkage inhibitor include lignin, lignin sulfonic acid, synthetic organic shrinkage inhibitors (such as formaldehyde condensates of phenol compounds), etc. The negative electrode material may contain one type of organic shrinkage inhibitor, or may contain two or more types.
[0088] The content of the organic shrink-preventing agent in the negative electrode material is, for example, 0.01% by mass or more, and, for example, 1.2% by mass or less.
[0089] Examples of the carbonaceous material include carbon black, graphite (artificial graphite, natural graphite, etc.), hard carbon, soft carbon, etc. The negative electrode material may contain one type of carbonaceous material or may contain two or more types of carbonaceous materials.
[0090] The content of the carbonaceous material in the negative electrode material is, for example, 0.1 mass % or more. The content of the carbonaceous material may be, for example, 3.5 mass % or less.
[0091] Examples of reinforcing materials include fibers (inorganic fibers, organic fibers, etc.). Examples of resins (or polymers) constituting the organic fibers include at least one selected from the group consisting of acrylic resins, polyolefin resins (polypropylene resins, polyethylene resins, etc.), polyester resins (including polyalkylene arylates (polyethylene terephthalate, etc.)), and celluloses (cellulose, cellulose derivatives (cellulose ether, cellulose ester, etc.)). Celluloses also include rayon.
[0092] The content of the reinforcing material in the negative electrode material is, for example, 0.03 mass % or more, and the content of the reinforcing material in the negative electrode material is, for example, 0.6 mass % or less.
[0093] (Analysis of negative electrode materials or their components) The following describes the quantitative analysis of the organic shrinkage inhibitor, carbonaceous material, barium sulfate particles, and reinforcing material in the negative electrode material, and the measurement of the size of the barium sulfate particles. The quantitative analysis of the components of the negative electrode material is performed using the negative electrode material sampled from the negative plate taken out of a fully charged lead-acid battery.
[0094] The negative electrode material is recovered from the negative plate in the following procedure. First, a fully charged lead-acid battery is disassembled to obtain the negative plate to be analyzed. The obtained negative plate is washed with water to remove sulfuric acid from the negative plate. The washing is performed by pressing a pH test paper against the washed surface of the negative plate until it is confirmed that the color of the test paper does not change. However, the washing time is within 2 hours. The washed negative plate is dried at 60±5°C for about 6 hours in a reduced pressure environment. After drying, if the negative plate contains an adhesive material, the adhesive material is removed from the negative plate by peeling. Next, the negative electrode material is separated from the negative plate to obtain a sample (hereinafter referred to as sample C). Sample C is crushed as necessary and subjected to analysis.
[0095] Quantitative Analysis of Organic Shrink Resistant The crushed sample C is immersed in a 1 mol / L NaOH aqueous solution to extract the organic shrink-preventing agent. Insoluble components are removed by filtration from the NaOH aqueous solution containing the extracted organic shrink-preventing agent, and the filtrate (hereinafter also referred to as filtrate D) is collected.
[0096] A predetermined amount of filtrate D is measured, desalted, concentrated, and dried to obtain a powder of the organic shrink-preventing agent (hereinafter also referred to as sample E). Desalting is performed using a desalting column, by passing filtrate D through an ion exchange membrane, or by placing filtrate D in a dialysis tube and immersing it in distilled water.
[0097] The organic shrinkage inhibitor is identified by combining information obtained from the infrared spectrum of sample E, the ultraviolet-visible absorption spectrum of a solution obtained by dissolving sample E in distilled water or the like, the NMR spectrum of a solution obtained by dissolving sample F in a solvent such as heavy water, or information obtained from pyrolysis GC-MS, which can obtain information on the individual compounds that make up the substance.
[0098] The ultraviolet-visible absorption spectrum of the filtrate D is measured. The content of the organic shrink inhibitor in the negative electrode material is quantified from the spectral intensity, the calibration curve prepared in advance, the measured amount of the filtrate D, and the mass of the sample C. If the structural formula of the organic shrink inhibitor to be analyzed cannot be precisely identified and a calibration curve of the same organic shrink inhibitor cannot be used, a calibration curve is prepared using an available organic shrink inhibitor that exhibits a similar ultraviolet-visible absorption spectrum, infrared spectroscopy spectrum, NMR spectrum, etc. to the organic shrink inhibitor to be analyzed.
[0099] Quantitative determination of carbonaceous materials, barium sulfate particles, and reinforcing materials 50 mL of 20% nitric acid was added to 10 g of the crushed sample C, and the mixture was heated for about 20 minutes to dissolve the lead components as lead ions. The resulting solution was then filtered to separate out the solids such as carbonaceous materials and barium sulfate.
[0100] The obtained solid content is dispersed in water to prepare a dispersion, and the reinforcing material is then collected from the dispersion using a sieve. The reinforcing material is washed with water, dried, and its mass is measured. The ratio (percentage) of the mass of the dried material to the mass of sample C is calculated. This ratio corresponds to the amount of reinforcing material in the negative electrode material.
[0101] The dispersion liquid from which the reinforcing material has been removed is subjected to suction filtration using a membrane filter whose mass has been measured in advance, and the membrane filter together with the filtered sample is dried in a dryer at 110°C ± 5°C. The resulting sample is a mixed sample of carbonaceous material and barium sulfate (hereinafter also referred to as Sample F). The mass of the membrane filter is subtracted from the total mass of Sample F and the membrane filter after drying to obtain the mass of Sample F (M m ) is measured. After that, the dried sample F is placed in a crucible together with the membrane filter and incinerated at 1300°C or higher. The remaining residue is barium oxide. The mass of barium oxide is converted to the mass of barium sulfate to obtain the mass of barium sulfate (M B ) is calculated. Mass M m From mass M B The mass of the carbonaceous material is calculated by subtracting the above.
[0102] <Particle size of barium sulfate particles> A predetermined amount of sample F is placed in a crucible and heated at 500°C under an oxygen atmosphere to convert the carbonaceous material into carbon dioxide and remove it. This allows barium sulfate to be recovered as a residue. Using the recovered barium sulfate (sample G), the volumetric particle size distribution of the barium sulfate particles is measured using a laser diffraction particle size distribution measuring device. As the laser diffraction particle size distribution measuring device, a Mastersizer 3000 manufactured by Malvern Panalytical is used. The average particle size of the barium sulfate particles is measured using a dispersion obtained by adding sample G to an aqueous sodium hexametaphosphate (NaHMP) solution (NaHMP concentration: 0.05 mass%) and performing ultrasonic dispersion for 1 minute. D10, D50 and D90 are obtained from the obtained particle size distribution. From these values, the span value is obtained using the above formula.
[0103] (Method of manufacturing negative electrode plate) The negative electrode plate can be formed by filling a negative electrode current collector with a negative electrode paste, aging and drying the negative electrode paste to prepare an unformed negative electrode plate, and then forming the unformed negative electrode plate. The negative electrode paste is prepared by adding water and sulfuric acid to lead powder, barium sulfate powder, an organic shrinkage inhibitor, and various additives as necessary, and kneading the mixture. For example, by using barium sulfate powder as a raw material from which barium sulfate particles with large particle diameters and barium sulfate particles with small particle diameters have been removed by classifying the barium sulfate powder, the span value of the barium sulfate particles in the negative electrode material can be reduced. In addition, when synthesizing barium sulfate powder, the particle diameter and particle diameter distribution of the powder may be adjusted by adjusting the reaction conditions. Note that the negative electrode active material in the charged state is sponge-like lead, but the unformed negative electrode plate is usually prepared using lead powder. In the aging process, it is preferable to age the unformed negative electrode plate at a temperature higher than room temperature and at a high humidity.
[0104] The formation can be carried out by immersing the plate group including the unformed negative plate in an electrolyte containing sulfuric acid in a lead-acid battery container and charging the plate group. However, the formation may be carried out before assembling the lead-acid battery or the plate group. The formation produces spongy lead.
[0105] (Positive plate) A paste-type positive electrode plate is used as the positive electrode plate. The paste-type positive electrode plate includes a positive electrode collector and a positive electrode material. The positive electrode material is held by the positive electrode collector. The positive electrode material is the portion of the positive electrode plate excluding the positive electrode collector. Note that a member such as a mat or pasting paper may be attached to the electrode plate. Such a member (also called an attachment member) is used integrally with the electrode plate, and is therefore included in the electrode plate. When the positive electrode plate includes an attachment member, the positive electrode material is the portion of the positive electrode plate excluding the positive electrode collector and the attachment member.
[0106] The positive electrode current collector included in the positive electrode plate may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead or lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the positive electrode current collector because it is easy to support the positive electrode material.
[0107] As the lead alloy used for the positive electrode current collector, a Pb-Ca alloy or a Pb-Ca-Sn alloy is preferable in terms of corrosion resistance and mechanical strength. The positive electrode current collector may have lead alloy layers with different compositions, and the alloy layer may be one layer or multiple layers.
[0108] The positive electrode material contained in the positive electrode plate contains a positive electrode active material (lead dioxide or lead sulfate) that develops capacity through an oxidation-reduction reaction. The positive electrode material may contain other additives (such as a reinforcing material) as necessary.
[0109] Examples of the reinforcing material include fibers (inorganic fibers, organic fibers (such as organic fibers made of resin described as the reinforcing material for the negative electrode material)).
[0110] The content of the reinforcing material in the positive electrode material is, for example, 0.03 mass % or more, and, for example, the content of the reinforcing material in the positive electrode material is, for example, 0.5 mass % or less.
[0111] Unformed paste-type positive plate is obtained by filling a positive current collector with a positive paste, aging and drying it. The positive paste is prepared by adding water and sulfuric acid to lead powder, an antimony compound, and other additives (such as reinforcing materials) as necessary, and kneading them.
[0112] A positive plate is obtained by chemically forming an unformed positive plate. Chemical formation can be performed by immersing an electrode plate group including an unformed positive plate in an electrolyte containing sulfuric acid in a battery container of a lead-acid battery and charging the electrode plate group. However, chemical formation may be performed before assembling the lead-acid battery or the electrode plate group.
[0113] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid. The electrolyte may be gelled as necessary.
[0114] The electrolyte may further contain at least one metal ion selected from the group consisting of Na ions, Li ions, Mg ions, and Al ions.
[0115] The specific gravity of the electrolyte at 20° C. is, for example, 1.10 or more. The specific gravity of the electrolyte at 20° C. may be 1.35 or less. Note that these specific gravities are values for the electrolyte of a lead-acid battery in a fully charged state.
[0116] The items described in this specification can be combined in any manner.
[0117] The method for evaluating IS life performance will be explained below. Based on SBA S 0101:2014, the IS life test is performed according to the following procedure. a) Throughout the entire test period, the battery shall be placed in an air atmosphere at 25±2°C. The wind speed in the vicinity of the battery shall be 2.0 m / s or less. b) The battery is connected to a life test device and discharged (Discharge 1 and Discharge 2) and charged as follows. This discharge and charge is counted as one discharge and charge cycle. The discharge and charge cycle is then continuously repeated. Discharge: Discharge 1 Discharge current I D ±1A for 59.0±0.2 seconds (where I D Calculate using the following formula and round off to the first decimal place. D =18.3×I 20 ) Discharge 2 Discharge current 300±1A for 1.0±0.2 seconds Charging: 60.0±0.3 seconds at charging voltage 14.00±0.03V (limited current 100.0±0.5A) After every 3600 cycles, leave the machine for 40-48 hours before starting the cycle again. Do not hold water until the 30,000th cycle. The end-of-discharge voltage (terminal voltage) of discharge 2 is measured, and the number of cycles until it reaches 7.2V is calculated and used as an index of IS life performance.
[0118] FIG. 1 shows the external appearance of an example of a lead-acid battery according to an embodiment of the present invention. The lead-acid battery 1 includes a battery case 12 that contains a plate group 11 and an electrolyte (not shown). The battery case 12 is divided into a plurality of cell chambers 14 by partition walls 13. Each cell chamber 14 contains one plate group 11. The opening of the battery case 12 is closed by a lid 15 that has a negative electrode terminal 16 and a positive electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When refilling with water, the vent plug 18 is removed and refilling liquid is added. The vent plug 18 may have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.
[0119] Each electrode plate group 11 is formed by stacking a plurality of negative electrode plates 2 and positive electrode plates 3 with a separator 4 interposed therebetween. Here, a pouch-shaped separator 4 that accommodates the negative electrode plates 2 is shown, but the shape of the separator is not particularly limited. In a cell chamber 14 located at one end of the battery case 12, a negative electrode shelf portion 6 that connects a plurality of negative electrode plates 2 in parallel is connected to a through connector 8, and a positive electrode shelf portion 5 that connects a plurality of positive electrode plates 3 in parallel is connected to a positive electrode column 7. The positive electrode column 7 is connected to a positive electrode terminal 17 outside the lid 15. In a cell chamber 14 located at the other end of the battery case 12, a negative electrode column 9 is connected to the negative electrode shelf portion 6, and a through connector 8 is connected to the positive electrode shelf portion 5. The negative electrode column 9 is connected to a negative electrode terminal 16 outside the lid 15. Each through connector 8 passes through a through hole provided in the partition wall 13 to connect the electrode plate groups 11 of adjacent cell chambers 14 in series.
[0120] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0121] Lead-acid batteries E1 to E14 and C1 to C15 Each lead-acid battery was prepared according to the following procedure. (1) Preparation of the separator A resin composition containing 100 parts by mass of polyethylene, about 160 parts by mass of silica particles, about 80 parts by mass of paraffin-based oil as a pore-forming agent, and 2 parts by mass of a penetrating agent was extruded into a sheet, stretched, and then a part of the pore-forming agent was removed to produce a microporous membrane having ribs on one side. At this time, the cooling rate of the extruded sheet and the stretching ratio were adjusted so that the crystallinity of the separator obtained by the above-mentioned procedure was the value shown in Table 1. In addition, the amount of silica particles and pore-forming agent relative to polyethylene was adjusted, and the amount of pore-forming agent removed was adjusted so that the first pore volume Vt and oil content obtained by the above-mentioned procedure were the values shown in Table 1.
[0122] The content of silica particles determined by the above procedure was about 60% by mass. The height of the rib determined by the above procedure was 0.6 mm. The thickness of the separator (thickness of the base portion) determined by the above procedure was 0.2 mm.
[0123] Next, the sheet-like microporous membrane was folded in half so that the ribs were disposed on the outer surface to form a bag, and the overlapping ends were crimped to obtain a bag-like separator.
[0124] The crystallinity, first pore volume Vt, oil content, silica particle content, base thickness, and rib height of the separator are values obtained for the separator before the lead-acid battery was fabricated, but are almost the same as the values measured by the above-mentioned procedure for the separator removed from the lead-acid battery after fabrication.
[0125] (2) Preparation of the positive electrode plate A positive electrode paste was prepared by mixing lead oxide, reinforcing material (synthetic resin fiber), water and sulfuric acid. The positive electrode paste was filled into the mesh of an expanded grid made of a Pb-Ca-Sn alloy that does not contain antimony, and then aged and dried to obtain an unformed positive electrode plate with a width of 100 mm, a height of 115 mm and a thickness of 1.6 mm.
[0126] (3) Preparation of negative electrode plate A negative electrode paste was prepared by mixing lead oxide, carbon black, barium sulfate powder, lignin, reinforcing material (synthetic resin fiber), water and sulfuric acid. The barium sulfate powder had an average particle size D50 of 0.6 μm, and was classified to remove small and large particles as necessary. The span value was adjusted by adjusting the particle size of the particles to be removed.
[0127] The negative electrode paste was filled into the mesh of an expanded lattice made of a Pb-Ca-Sn alloy, aged, and dried to obtain an unformed negative electrode plate (width 100 mm, height 115 mm, thickness 1.2 mm). The amounts of carbon black, lignin, and synthetic resin fiber were adjusted to 0.3 mass%, 0.1 mass%, and 0.1 mass%, respectively, when measured in a fully charged state after formation. The amount of dispersion liquid added was adjusted so that the amount of barium sulfate was 2.1 mass parts per 100 mass parts of powder mainly composed of lead oxide.
[0128] (4) Preparation of lead-acid battery The unformed negative electrode plates were housed in a pouch-shaped separator and stacked with the positive electrode plates to form an electrode plate group consisting of seven unformed negative electrode plates and six unformed positive electrode plates.
[0129] The lugs of the positive plates and the lugs of the negative plates were welded to the positive and negative shelf parts, respectively, using the cast-on-strap method. The plate group was inserted into a polypropylene battery case, electrolyte was poured in, and chemical formation was performed inside the battery case to assemble a flooded lead-acid battery with a rated voltage of 12V and a rated capacity of 30Ah (5-hour rate capacity (capacity when discharged at a current (A) that is 1 / 5 of the Ah value indicated on the rated capacity)). Six plate groups were connected in series inside the battery case.
[0130] The electrolyte used was an aqueous sulfuric acid solution. The specific gravity of the electrolyte after formation at 20°C was 1.285.
[0131] (5) Evaluation The XRD spectrum of the separator of the lead-acid battery E1 measured by the above-mentioned procedure is shown in Figure 2. As shown in Figure 2, a diffraction peak corresponding to the (110) plane of the crystalline region of polyethylene was observed in the range of 2θ = 21.5° to 22.5°, and a diffraction peak corresponding to the (200) plane was observed in the range of 2θ = 23° to 24.5°. A halo due to the amorphous region was observed broadly in the wide range of 2θ = 17° to 27°.
[0132] The IS life performance was evaluated using the obtained lead-acid batteries by the procedure described above, and the span value of barium sulfate particles in the negative electrode material was measured by the procedure described above. The IS life performance was evaluated by the ratio (%) of the number of cycles of each lead-acid battery to the number of cycles of the lead-acid battery C7, which was set as 100 (%).
[0133] The evaluation results of IS life performance are shown in Table 1. In the table, E1 to E14 are examples, and C1 to C15 are comparative examples.
[0134] [Table 1]
[0135] As shown in Table 1, when the crystallinity of the separator was less than 20%, the IS life performance was generally low even if the first pore volume Vt changed, and the larger Vt was, the lower the IS life performance became.
[0136] In contrast, when the crystallinity of the separator is 20% or more, Vt is 0.8 cm 3 / g or more, high IS life performance was obtained even if the span value of the barium sulfate particles was large. It can be seen that high IS life performance can be ensured if the span value is 2.78 or less, and the smaller the span value, the higher the IS life performance tends to be. It can also be seen that the higher the crystallinity of the separator, the higher the IS life performance tends to be. [Industrial Applicability]
[0137] The lead-acid battery according to the above aspect of the present invention is suitable for use as an IS power source (such as a lead-acid battery for an idling stop system vehicle) and as a starting power source for various vehicles (such as automobiles and motorcycles). The lead-acid battery can also be suitably used as a power source for industrial power storage devices such as electric vehicles (such as forklifts). Note that these uses are merely examples. The uses of the lead-acid battery according to the above aspect of the present invention are not limited to these. [Explanation of symbols]
[0138] 1:Lead acid battery 2: Negative plate 3: Positive plate 4: Separator 5: Positive electrode shelf 6: Negative electrode shelf 7: Positive pole 8: Through connector 9: Negative pole 11: Plate group 12:Battery container 13: Bulkhead 14: Cell Room 15: Lid 16: Negative terminal 17: Positive terminal 18: Liquid outlet plug
Claims
1. A lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate, the negative plate comprises a negative electrode material including barium sulfate particles; In the volume-based particle size distribution of the barium sulfate particles, when particle sizes at which the cumulative frequency is 10%, 50% and 90% are D10, D50 and D90, respectively, a span value expressed by (D90-D10) / D50 is 2.78 or less; The separator includes a crystalline region and an amorphous region, In the X-ray diffraction spectrum of the separator, 100×I c / (I c +I a ) has a crystallinity of 20% or more, I c is the integrated intensity of the diffraction peak having the maximum peak height among the diffraction peaks corresponding to the crystalline region, I a is the integrated intensity of the halo corresponding to the amorphous region, In the separator, the total volume Vt of the pores having a pore diameter of 0.005 μm or more and 10 μm or less is 0.8 cm 3 / g or more.
2. 2. The lead acid battery of claim 1, wherein the span value is less than or equal to 2.
75.
3. The total volume Vt is 0.90 cm 3 The lead acid battery according to claim 1 or 2, wherein the CdSe is 0.1 to 0.5 μm.
4. The lead acid battery according to any one of claims 1 to 3, wherein the crystallinity is 40% or less.
5. The lead acid battery according to any one of claims 1 to 4, wherein the separator contains a polyolefin.
6. The polyolefin contains at least ethylene units, 6. The lead acid battery of claim 5, wherein the diffraction peak having the maximum peak height corresponds to a (110) plane of the crystalline domain.
7. The lead-acid battery according to any one of claims 1 to 6, wherein the separator has a thickness of 100 µm or more and 300 µm or less.
8. The lead acid battery according to any one of claims 1 to 7, wherein the separator contains oil.
Citation Information
Patent Citations
Negative electrode plate for lead storage batteries and lead storage battery
JP2015109171A
Improved separator for reinforced flooded batteries, batteries, and related methods
JP2019514173A
Lead-acid battery
JP2021068551A
Separator for lead storage battery and lead storage battery including the same
JP2022186309A
Lead storage battery and production method therefor
WO2018100635A1